Modelo de Gestión Estratégica de Proyectos para la Municipalidad de Turrialba - Valladares-Rosado, Paola (Instituto Tecnológico de Costa Rica, 2016)
This project aims to elaborate a Model of Strategic Project Management for Turrialba´s municipality. It provides with tools that facilitate the execution under order and methodology that improves the efficiency during the application of the projects. It started with the analysis of the current situation of the municipality in relation to the project management. For that, an interest group mapping was carried out. Once they were identified, an instrument was applied which helped to identify the needs in terms of procedures, techniques and performance of the involved members. Each of the units that were analyzed showed the limitations a lack of knowledge that exists relating the project topic. Besides, they showed that it is a main activity done by the municipality. The proposal of the strategic project management model includes standardization formats about the dealing of each project, the work template designs which targets to foster a higher efficiency in daily tasks. The Municipality´s Canvas Business Model incorporates is incorporated as a way to have better clarity about what the institution makes allowing the municipal project management to become a functional activity for Turrialba county´s development. A socialization project is developed. This guide the different units toward the usage of the proposed tools to establish a project culture as a transversal action axis for all involved people. To conclude, although Turrialba´s municipality develops a high amount of its administration through projects, internally it lacks the basic requirements to show effectiveness in its activities; thus, it´s recommended to use this Model of Strategic Project Management.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2016.
Keywords: Metodología; Eficacia; Eficiencia; Organización; Gobierno Municipal; Ayuntamientos; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies